The polar and lateral flagella from Plesiomonas shigelloides are glycosylated with legionaminic acid - Merino, Susana; Aquilini, Eleonora; Fulton, Kelly M.; Twine, Susan M.; Tomás, Juan M. (Frontiers in Microbiology, 2015)
Plesiomonas shigelloides is the unique member of the Enterobacteriaceae family able to produce polar flagella when grow in liquid medium and lateral flagella when grown in solid or semisolid media. In this study on P. shigelloides 302-73 strain, we found two different gene clusters, one exclusively for the lateral flagella biosynthesis and the other one containing the biosynthetic polar flagella genes with additional putative glycosylation genes. P. shigelloides is the first Enterobacteriaceae were a complete lateral flagella cluster leading to a lateral flagella production is described. We also show that both flagella in P. shigelloides 302-73 strain are glycosylated by a derivative of legionaminic acid (Leg), which explains the presence of Leg pathway genes between the two polar flagella regions in their biosynthetic gene cluster. It is the first bacterium reported with O-glycosylated Leg in both polar and lateral flagella. The flagella O-glycosylation is essential for bacterial flagella formation, either polar or lateral, because gene mutants on the biosynthesis of Leg are non-flagellated. Furthermore, the presence of the lateral flagella cluster and Leg O-flagella glycosylation genes are widely spread features among the P. shigelloides strains tested.